Investigating the Effect of Problem-Based Learning on Students’ Recount Writing Skills in an Indonesian EFL Classroom - Dewi Aprillavien Syahrani; Andrian Nuriza Johan; Basuki (FOSTER: Journal of English Language Teaching, 2026)
Writing is a challenging skill for students in English as a Foreign Language (EFL) contexts, particularly in producing recount texts due to difficulties in generating ideas, organizing content, and applying appropriate language features. This study aims to investigate the effect of Problem-Based Learning (PBL) on students’ recount text writing skills. A quantitative pre-experimental design with a one-group pretest–posttest approach was employed, involving 32 tenth-grade students. The data were collected through writing tests and analyzed using descriptive and inferential statistics, including the Wilcoxon Signed-Rank Test. The findings revealed a statistically significant difference between pre-test and post-test scores; however, the results indicated a decline in students’ writing performance after the implementation of PBL. This suggests that PBL, in this context, was not effective in improving students’ recount text writing skills. The findings highlight that the effectiveness of PBL is influenced by factors such as the duration of implementation, the level of instructional scaffolding, and students’ readiness to engage in student-centered learning. Therefore, it is recommended that PBL be implemented gradually with sufficient guidance and longer duration to achieve optimal results. This study contributes to the understanding of the practical challenges in applying student-centered learning approaches in EFL writing classrooms.